2006
DOI: 10.1097/01.jom.0000218701.62658.a2
|View full text |Cite
|
Sign up to set email alerts
|

A Cohort Mortality Study of Employees in the U.S. Carbon Black Industry

Abstract: Employment in carbon black production in the United States seems not to be associated with increased mortality overall, cancer overall and, in particular, lung cancer. Further research, however, incorporating a detailed exposure assessment is needed to determine whether exposure to carbon black at high levels may be associated with an increased risk of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…The carcinogenicity of CB in humans has been evaluated in a limited number of epidemiologic studies, including among CB production workers in the United Kingdom [Hodgson and Jones, ; Sorahan et al, ], Germany [Buchte et al, ; Wellmann et al, ], and the United States [Robertson and Inman, ; Dell et al, ]. While results from these studies have provided some evidence of an excess of lung cancer among CB‐exposed workers, the association is inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…The carcinogenicity of CB in humans has been evaluated in a limited number of epidemiologic studies, including among CB production workers in the United Kingdom [Hodgson and Jones, ; Sorahan et al, ], Germany [Buchte et al, ; Wellmann et al, ], and the United States [Robertson and Inman, ; Dell et al, ]. While results from these studies have provided some evidence of an excess of lung cancer among CB‐exposed workers, the association is inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…An update of the UK study [Sorahan et al, 2001] found a significantly elevated SMR for lung cancer (SMR 173, Obs 61) but no significant trends of lung cancer risks increasing with estimated cumulative exposure to carbon black (lifetime exposure or exposures received more than 20 years ago) was found. The earlier US work had not been carried out on a defined cohort; this limitation has now been rectified [Dell et al, 2006]. The newly defined US cohort of some 5,000 carbon black workers from 18 facilities failed, however, to show any excess of lung cancer (SMR 97,Obs 138).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a dose–response exposure analysis is under way on the U.S. carbon black cohort (> 5,000 production workers). An earlier evaluation of this cohort showed no increase in any type of cancer (Dell et al 2006). …”
mentioning
confidence: 53%